Simultaneous Association between Quality of Corporate Environmental Performance and Financial Performance: Evidence from Select Asian Countries - Santi Gopal Maji; Utpal Kumar De; Ardi Gunardi (Universitas Pasundan, 2020)
This study empirically investigates the simultaneous association between the quality of environmental performance (EP) and financial performance of firms selected from three Asian countries' Japan, South Korea, and India. The content analysis technique based on a four-point scale was used to measure the quality of EP, whereas financial performance was measured based on the market-to-book ratio. Employing system generalized method of moments and fixed effects regression model in a system of two-equation model, the study finds that EP has a positive impact on financial performance. Similarly, the financial performance has a positive influence on the quality of EP. The findings of the study indicate that a firm can enhance its overall financial performance by improving its EP. This implies that firms not only improve their economic performance through environmentally responsible business practices, but also help in fulfilling some of the sustainable development goals of the United Nation's 2030 development agenda.